The Influence of Career Adaptability and Willingness to Compromise on Work Readiness: A Study of Student’s School to Work Transition in Supporting SDG 4 - Mega Iswari; Afdal Afdal; Nurfarhanah Nurfarhanah; Nurhastuti Nurhastuti; Humaira Mustika; Ringgi Rahmat Fitra (Journal of Current Studies in SDGs, 2027)
Objective: The transition from higher education to the workplace represents a critical stage that requires students to possess adequate psychological resources and career competencies. This study aims to examine the influence of career adaptability and willingness to compromise on students’ work readiness during the school-to-work transition while highlighting its contribution to SDG 4 (Quality Education) through the development of employability competencies. Method: This study employed a quantitative descriptive approach using a correlational research design. The population consisted of 119,260 university students from seven universities in West Sumatra, Indonesia. A total of 210 students were selected using incidental sampling techniques. Data were collected using career adaptability, willingness to compromise, and work readiness instruments. Data analysis was conducted using descriptive statistics, simple linear regression, and multiple linear regression analysis.  Results:  The findings indicate that students demonstrated high levels of career adaptability and willingness to compromise, while their work readiness was categorized as moderate. Career adaptability significantly contributed to work readiness by 24.1%, while willingness to compromise contributed 11.3%. Simultaneously, both variables explained 27.5% of the variance in students’ work readiness.  Novelty: This study highlights the importance of strengthening career adaptability as an educational strategy to improve graduate employability and support SDG 4 by promoting quality education that prepares students for sustainable career development.